Citrus pests in a global world - Urbaneja, Alberto; Grout, Tim G.; Gravena, Santin; Wu, Fengnian; Cen, Yijing; Stansly, Philip A. (Elsevier, 2021)
Citrus pest management has evolved from a primarily biological approach to dependence on chemical control, followed by more integrated systems. More recently, the spread of huanglongbing (HLB) or citrus greening disease in Asia and both Americas has compromised integrated pest management (IPM) by requiring multiple applications of broad-spectrum insecticides to control the psyllid vector. In contrast, IPM is more the norm in the Mediterranean region and Australia where HLB vector psyllids are not yet established. Another major factor determining the exigencies of citrus pest management is the fresh vs process fruit dichotomy, which dictates the level of control required to produce a saleable product. Thus, the major citrus industries have to struggle with the apparent contrary demands of producing an affordable and healthy product, with no pesticide residues, fruit free of phytosanitary pests and blemishes, while still remaining profitable. Success in meeting these challenges will determine whether citrus can maintain its place as a premier tree fruit crop worldwide. In this chapter, we briefly present pest issues and management strategies from the five most important citrus production areas: Asia, the Mediterranean basin, North America, South America, and Africa.